2014
DOI: 10.1071/wf13150
|View full text |Cite
|
Sign up to set email alerts
|

Successional stage after land abandonment modulates fire severity and post-fire recovery in a Mediterranean mountain landscape

Abstract: This study analyses the effect of successional stage after farmland terrace abandonment on post-fire plant recovery in a Mediterranean landscape. Specific objectives of the study were to (1) compare fuel characteristics and fire severity in three successional stages after farmland abandonment – dry grassland, dense shrubland and pine stands; (2) analyse the effect of pre-fire successional stage and fire severity on vegetation recovery and (3) analyse the relative vulnerability (i.e. potential for ecosystem shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…3), short-term simulations were technically 'transient', showing large variability in plant composition between simulations, mainly depending on initial conditions and the specific stochastic fire sequence realized in each simulation. In old fields, assemblies of shrubs and pines without oaks prevail under the current fire regime Pausas & Lloret, 2007;L opez-Poma et al, 2014), with pine disappearing under repeated fires (Daskalakou & Thanos, 1996;Eugenio & Lloret, 2004). first century in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), short-term simulations were technically 'transient', showing large variability in plant composition between simulations, mainly depending on initial conditions and the specific stochastic fire sequence realized in each simulation. In old fields, assemblies of shrubs and pines without oaks prevail under the current fire regime Pausas & Lloret, 2007;L opez-Poma et al, 2014), with pine disappearing under repeated fires (Daskalakou & Thanos, 1996;Eugenio & Lloret, 2004). first century in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was sufficiently accurate as it was found that the main limitation to pine persistence was fire recurrence and associated post-fire availability of pine seeds (Thanos & Daskalakou, 2000;Baeza et al, 2007;Tucker & Cadotte, 2013;L opez-Poma et al, 2014): in the present model, pines could not survive even when they were competitively favoured over oaks, if two fires would occur too close to each other (i.e. This approach was sufficiently accurate as it was found that the main limitation to pine persistence was fire recurrence and associated post-fire availability of pine seeds (Thanos & Daskalakou, 2000;Baeza et al, 2007;Tucker & Cadotte, 2013;L opez-Poma et al, 2014): in the present model, pines could not survive even when they were competitively favoured over oaks, if two fires would occur too close to each other (i.e.…”
Section: Researchmentioning
confidence: 99%
“…, López‐Poma et al. ). We studied the effects of a large wildfire on vegetation structure within dry sclerophyll forest, woodland and heath vegetation types, where a variable mosaic of fire histories had previously been established.…”
Section: Discussionmentioning
confidence: 99%
“…Land degradation in the Mediterranean is a multifaceted process that results from the independent or combined effect of factors such as land cover conversion (Alphan ), agriculture and rangeland mismanagement (Cerdà et al ; García‐Orenes et al ), and frequent or severe wildfires (Guénon et al ; López‐Poma et al ), which are ultimately driven by social and economic changes (Abu Hammad & Tumeizi ) and often lead to soil erosion (Cerdà et al ) and long‐term loss of natural vegetation (FAO ). Specifically for rangelands, overgrazing is considered as the key degradation factor in many regions of the world, as it results in increased soil and water losses, decrease and degradation of the vegetation cover and critical changes in regulating ecosystem services (Cerdà & Lavee ; Mekuria & Aynekulu ; Angassa ).…”
Section: Introductionmentioning
confidence: 99%